GASTRONOMY OFFER IN A FUNCTION OF CREATION AND CO-CREATION OF A RECOGNIZED HOTEL BRAND - ILLUSTRATIONS FROM HOTEL CRNI VRH - Gajić, Tamara; Zrnić, Miloš; Vujić, Tamara; Vujić, Milan; Stojanović, Djorđe (Economics of Agriculture, 2022)
The aim of the paper is to point out the possibility of the inﬂuence of the quality of the gastronomic offer in the restaurant of the hotel Crni vrh, on the creation or co creation of the hotel brand. The quality items of the hotel’s complete catering offer were analyzed and grouped by exploratory factor analysis into three factors (Food, Space and Personality). The results of the multiple regression analysis determined the contribution of two quality factors to the creation of the hotel brand. Also, the research came to the conclusion that the majority of visitors, after the experience gained, decide to come again to the rural and mountainous areas, and a smaller percentage to the urban environment. The importance of the research is reﬂected in the contribution of the existing literature, in the contribution to future more important research, as well as in finding strategic solutions for better hotel operations.